‘What hath God wrought’: Dystopia, Empathy and Revolution in Naomi Alderman’s The Future - Yebra, José M. (Complutense Journal of English Studies, 2025)
. This article delves into Naomi Alderman’s The Future (2023), a sci-fi feminist dystopia that revisits and updates her previous novel, The Power (2017). Whereas in The Power, a cataclysm turns gender roles upside down, The Future goes further as it seemingly features the end of Western neo-liberalism and civilization. In the Capitalocene envisaged in The Future, there are still a few survivalists, i.e. nomad characters in a pluriversal scenario, who contest the new order (a continuation of its predecessor) and struggle for an ethical one based on a partnership model where empathy and a liberating revolution can replace a hierarchical and exterminist paradigm. Yet, this paper argues, this dystopia recalls Alderman’s previous fiction: it is at once parodic, devastating and especially cautionary because the system which intends to replace the current techno-dystopia can be easily corrupted. As the analysis of the novel shows, a dystopian regime is cyclically replaced by a similar one in the Capitalocene. To explore Alderman’s latest dystopia and its redeeming features, this essay considers Riane Eisler’s “dominator” and “partnership” models, Jeremy Rifkin’s conception of empathy, and Hannah Arendt’s idea of revolution.